A Somaesthetics of Performative Beauty Tangoing Desire and Nostalgia - Heinrich, Falk (Taylor & Francis, 2023)
actions, aesthetics, Argentine tango, awareness, dance studies, enactivism, eros, Falk Heinrich, freedom, grace, movements, performance studies, performative beauty, phenomenology, poiesis, social dancing, somaesthetics